Transcriptome Changes and Potential Immunotoxicity Analysis in RAW264.7 Macrophages Caused by Bisphenol F - Chen, Huiling; Zhang, Yanchao; Li, Xing; Zhang, Wei; He, Haoqi; Du, Bohai; Li, Tianlan; Tang, Huanwen; Liu, Yungang; Li, Li; Shi, Ming (Frontiers in Pharmacology, 2022)
As a viable substitute for bisphenol A (BPA), BPF has been widely used in the plastic industry and daily consumer goods, resulting in its detection in humans at a comparable concentration. Evidence reveals that BPF and BPA may have similar toxic effects due to their similar structures. However, there is less information about BPF and its latent implications on the immune system, which is associated with many disorders. In this study, the in vitro toxicity of BPF on RAW264.7 macrophages was explored. The cells were treated with different concentration of BPF (5, 10, 20, 50, 100 and 200 μM), the cell viability and apoptosis were detected, the gene expression profile was analyzed by whole-transcriptome sequencing and the mRNA levels were detected by qRT-PCR. The results showed high concentration of BPF could significantly reduce the survival rate of RAW264.7 macrophages. Although the medium concentration (20-50 μM) of BPF seemed have no impact on the cell activity of macrophages, it caused the occurrence of apoptosis. The results of differential transcription showed that compared with the control group, 121 genes were up-regulated and 82 genes were down-regulated in BPF group. The significantly changed gene functions were mainly concentrated in cell cycle, phagosome, lysosome, antigen processing and presentation. These findings provide valuable information for correctly understanding the immunotoxicity risk of BPF and may help to improve the hazard identification of bisphenol compounds.